1990
DOI: 10.1177/0148607190014006640
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Hepatic Mitochondrial Function during Total Parenteral Nutrition in Immature Rats

Abstract: To evaluate the effects of total parenteral nutrition (TPN) on hepatic mitochondrial function in immature rats, changes in hepatic energy charge levels and oxidative phosphorylation rates of hepatic mitochondria were studied along with the examination of serum chemical test. Male Wistar rats weighing 30 to 45 g were used and randomized into TPN (n = 8), enteral (n = 7), and control groups (n = 8). Parenteral and enteral groups were fed with TPN solution containing 19.3% dextrose, 3.19% amino acids, 1.05% fat e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…In cases of liver cirrhosis, fatty liver, or injury from xenobiotics, oxidative metabolism of various substrates is impaired because of the dysfunction of the electron transport chain in hepatic mitochondria [9,10]. A study designed to evaluate mitochondrial function in immature rats suggested that PN use induced marked metabolic changes to the mitochondria leading to deficiencies in mitochondrial phosphorylation and respiratory chain function compared to a control group [11]. …”
mentioning
confidence: 99%
“…In cases of liver cirrhosis, fatty liver, or injury from xenobiotics, oxidative metabolism of various substrates is impaired because of the dysfunction of the electron transport chain in hepatic mitochondria [9,10]. A study designed to evaluate mitochondrial function in immature rats suggested that PN use induced marked metabolic changes to the mitochondria leading to deficiencies in mitochondrial phosphorylation and respiratory chain function compared to a control group [11]. …”
mentioning
confidence: 99%
“…12 With the administration of TPN, changes in liver metabolism occur, resulting in a decreased lipoprotein and drug metabolism.3 1 ,3'2 Prolonged administration of TPN eventually results in hepatomegaly and elevated liver lipids not consistently observed in enterally fed animals, which may result in impairment of hepatic function. [32][33][34][35] As demonstrated in this study, there was an increase in liver lipid in both the TB-TPN and TB-EN groups, although the increase was greater in the TB-TPN group.…”
Section: Discussionmentioning
confidence: 81%
“…10,11 Little information is available, however, to explain the mechanism whereby d-TPN attenuates postoperative liver injury, although possible effects on hepatic mitochondrial function have been postulated. 12 Katayama et al 12 reported that continuous TPN (c-TPN) resulted in decreased hepatic energy charge and rates of oxidative phosphorylation in the hepatic mitochondria of immature rats, and speculated that this deterioration in mitochondrial function may contribute to hepatic dysfunction in infants. Because cholestasis, a major hepatic complication of TPN in infants, is closely associated with adenosine triphosphate breakdown in hepatocytes, 13 it is not unreasonable to examine whether TPN may alter the susceptibility of mitochondrial function in the liver, particularly following surgical intervention.…”
Section: Although Discontinuous Total Parenteral Nutrition (D-tpn)mentioning
confidence: 99%